An Analysis of Teachers’ Teaching Strategies in Introducing Color and Shape Concepts to Children at Raudhatul Athfal Ibnu Rusyid - Ramadhani, Fitri Fauziah; Kusviantara, Livia Febriari Putri; Meirawati , Nastiti; Undayasari, Dwi; Abidin, Yunus (Seulanga : Jurnal Pendidikan Anak, 2025)
This study aims to describe implementation of teaching strategies by teachers in introducing the concepts of colors and shapes at RA (Raudhatul Athfal) Ibnu Rusyid, Bandung Regency. The research highlights the importance of early childhood education as a golden period of child development, where appropriate stimulation significantly influences cognitive, song, motor, and character development. Teachers as the main facilitators in early childhood education institutions are required to be able to apply learning strategies that are effective, fun and in accordance with the characteristics of children, especially in introducing basic concepts such as colors and shapes. The study employs a qualitative descriptive method with teachers at RA Ibnu Rushid as the subject. Data were collected through observations and interviews. The results indicate that the teachers applied various learning strategies, including expository, contextual, and problem-based approaches. Teachers provide concrete learning media such as color cards, blocks, and everyday objects to facilitate children's understanding of color and shape concepts. Additionally, learning activities involve playing, singing, and hard-on practice that actively engage children in the learning process. The conclusion of this study is that effective teaching strategies combined with appropriate media use are highly effective in introducing color and shape concepts to early childhood learners. This research contributes to the development of early childhood education learning strategies and serves as a reference for educators in designing enjoyable and meaningful learning experiences for children.